2013
DOI: 10.1080/09593330.2013.808243
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing acid mine drainage sludge and coal fly ash for phosphate removal from dairy wastewater

Abstract: This study aims to investigate a new and sustainable approach for the reuse of industrial by-products from wastewater treatment. The dairy industry produces huge volumes of wastewater, characterized by high levels of phosphate that can result in eutrophication and degradation of aquatic ecosystems. This study evaluated the application of acid mine drainage (AMD) sludge, coal fly ash, and lignite as low-cost adsorbents for the removal of phosphate from dairy wastewater. Material characterization using X-ray flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…e change in crystal structure of the unmodified and modified FAN particles is evaluated according to the XRD patterns presented in Figure 4. As reported in our previous research [21] and some other research studies [3][4][5]24], the XRD spectrum of the FA demonstrates that the structure of FA0 particles is composed of mullite, quartz, and hematite while the FAN particles has a zeolite P (Na 6 Al 6 Si 10 O 32 .12H 2 O or NaP) structure (at 2θ � 13°, 2θ � 16°, 2θ � 27°, and 2θ � 55°).…”
Section: Crystal Structure Of the Fan And Modified Fan Particlessupporting
confidence: 68%
“…e change in crystal structure of the unmodified and modified FAN particles is evaluated according to the XRD patterns presented in Figure 4. As reported in our previous research [21] and some other research studies [3][4][5]24], the XRD spectrum of the FA demonstrates that the structure of FA0 particles is composed of mullite, quartz, and hematite while the FAN particles has a zeolite P (Na 6 Al 6 Si 10 O 32 .12H 2 O or NaP) structure (at 2θ � 13°, 2θ � 16°, 2θ � 27°, and 2θ � 55°).…”
Section: Crystal Structure Of the Fan And Modified Fan Particlessupporting
confidence: 68%
“…Previous results showed that CFA provided a large surface area (212 m 2 g À1 ) and was composed of 12% merwinite (Ca 3 Mg(SiO 4 ) 2 ), 4% calcite (CaCO 3 ), and 2% portlandite (Ca(OH) 2 ). It also contained a large quantity of poorly crystalline (amorphous) Fe and Al oxides (5700 and 6760 mg kg À1 , respectively), which are equivalent to an acid neutralizing capacity of 54.3% CaCO 3 (Wang et al, 2013;.…”
Section: Field-contaminated Soil and Amendment Materialsmentioning
confidence: 99%
“…Biochar was produced by auger reactor, this treatment can reduce greenhouses gases and make energy balance (Brassard et al, 2018) Utilization of acid mine drainage sludge and coal fly ash for phosphate removal from dairy wastewater Acid mine drainage sludge and coal fly ash can be combined to reduce phosphate from wastewater. Acid mine drainage sludge can utilize to biochar to reduce phosphate (Y. R. Wang et al, 2013) Removal heavy metals from contaminated soil Biochar was pyrolized at 350 o C for a hour under 0.1 m 3 h -1 nitrogen flow, after this treatment biochar was prepared by steam activation at 800 °C for 45 min in an atmosphere with 71% water vapor in nitrogen. Biochar can remove heavy metals content such as Cu(II), Cd(II), and Ni(II) in soil polluted (Uchimiya et al, 2010) Effect of cassava waste biochar on sorption and release behavior of atrazine in soil Biochar was used to sorption and desorption test to remove atrazine in latosol.…”
Section: Statementmentioning
confidence: 99%